Consecutive Aminolithiation–Carbolithiation of a Linear Aminoalkene Bearing Terminal Vinyl Sulfide Moiety to Give Hydroindolizine - Yamamoto, Yasutomo; Yamaguchi, Tatsuya; Kaneshige, Atsunori; Hashimoto, Aiko; Kaibe, Sachiho; Miyawaki, Akari; Yamada, Ken-ichi; Tomioka, Kiyoshi (Synlett, 2017)
Aminolithiation–carbolithiation tandem cyclization of an aminoalkene bearing vinyl sulfide moiety proceeded smoothly using stoichiometric amounts of BuLi. Both aminolithiation and carbolithiation were in equilibrium at room temperature, and the stereochemistry of the cyclization was thermodynamically controlled. At –78 °C the reaction was kinetically controlled and the cyclized product, 1,2-disubstituted octahydroindolizine, was obtained with good diastereoselectivity.
Keywords: aminolithiation; carbolithiation; vinyl sulfide; N-heterocycles; domino reaction